Degenerate Oligonucleotide Primed–Polymerase Chain Reaction‐Based Chromosome Painting of P Genome Chromosomes in Agropyron cristatum and Wheat–A. cristatum Addition Lines. Issue 6 (1st November 2015) - Han, Haiming; Zhang, Yingxin; Liu, Weihua; Hu, Zanmin; Li, Lihui
ABSTRACT: Agropyron cristatum (L.) Gaertn. (2n = 4x = 28, PPPP), a wild relative of wheat, could provide many desirable genes for wheat improvement. Microdissection and degenerate oligonucleotide primed –polymerase chain reaction (DOP–PCR) is an effective way to isolate specific sequences. The development of specific sequences and functional markers of P genome could lay the foundation for gene mapping and cloning. In this study, chromosomes 6PS and 6PL were microdissected from wheat– A. cristatum 6PS and 6PL addition lines, and DOP–PCR products from both microdissected chromosomes were used as probes to hybridize with mitotic metaphase chromosomes of diploid A. cristatum, wheat– A. cristatum addition lines 6PS, 6PL, and 6P. The results showed that the distribution patterns on A. cristatum chromosomes using DOP–PCR products of microdissected 6PS as the probe were similar to those using DOP–PCR products of microdissected 6PL as the probe. They both distributed along all chromosomes, and chromosome 6P and other chromosomes were similar according to the hybridization pattern. There were no signals on wheat chromosomes indicating that DOP–PCR products contain P‐genome specific sequences. Actually, we obtained a P‐genome specific sequence from the DOP–PCR products of 6PS, which could be used as a fluoresence in situ hybridization (FISH) probe to identify P genome chromatin in wheat– A. cristatum introgression lines. These results could provide a basis for the study of structure and evolution of P genome chromosomes. Furthermore, this study may lead to mapping and cloning of the desirable genes on 6P chromosome.